Epigenetic Characteristics of Human Subtelomeres Vary in Cells Utilizing the Alternative Lengthening of Telomeres (ALT) Pathway - Toubiana, Shir (Life (Basel), 2021)
Most human cancers circumvent senescence by activating a telomere length maintenance mechanism, most commonly involving telomerase activation. A minority of cancers utilize the recombination-based alternative lengthening of telomeres (ALT) pathway. The exact requirements for unleashing normally repressed recombination at telomeres are yet unclear. Epigenetic modifications at telomeric regions were suggested to be pivotal for activating ALT; however, conflicting data exist regarding their exact nature and necessity. To uncover common ALT-positive epigenetic characteristics, we performed a comprehensive analysis of subtelomeric DNA methylation, histone modifications, and TERRA expression in several ALT-positive and ALT-negative cell lines. We found that subtelomeric DNA methylation does not differentiate between the ALT-positive and ALT-negative groups, and most of the analyzed subtelomeres within each group do not share common DNA methylation patterns. Additionally, similar TERRA levels were measured in the ALT-positive and ALT-negative groups, and TERRA levels varied significantly among the members of the ALT-positive group. Subtelomeric H3K4 and H3K9 trimethylation also differed significantly between samples in the ALT-positive group. Our findings do not support a common route by which epigenetic modifications activate telomeric recombination in ALT-positive cells, and thus, different therapeutic approaches will be necessary to overcome ALT-dependent cellular immortalization.